Hubungan Rotasi Kerja dan Kepuasan Kerja Dengan Komitmen Terhadap Organisasi - Giri Susilo Adi; Muhammad Thohar Arifin; Agus Santoso (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2015)
Backgroud: Organizational commitment is the core of human resourses management analisys. Hospital policy regarding the human resources management has become more important and it was implemented in increasing nurses commitment to the hospital through the job satisfaction and job rotation. Method: this quantitative reseach employed 137 associate nurses as respondent from 34 units at psychiatric hospital. A modified questionnaire was operated by the researcher with proper validity and reliability test and verified by the experts. The data were analyzed by Chi square test and logistic regression. Result: bivariate analysis found that job rotation and job satisfaction associated with the comitment to organization with p value 0.014 and 0.013 respectively. While multivariate analysis resulted the job rotation with p=0.028 and job satisfaction p=0.029 Conclusion: both job rotation and job satisfaction were significantly associated with the commitment to organization. Job satisfaction was the strongest variable which was correlated to the commitment to the organization.